The Scholarly Divide: Insights from the AIS Well-being Project - Wright, Ryan; Saunders, Carol; Sarker, Saonee; Kankanhalli, Atreyi; Whitley, Edgar; Tuunainen, Virpi; Henriksen, Helle (Communications of the Association for Information Systems, 2023)
This article provides an overview of the findings from the Information Systems (IS) Well-Being Project that was started in the fall of 2020. There were two goals of this project: 1) to understand the physical, mental, social, and financial well-being of IS academics during the COVID-19 pandemic, and 2) to theorize the downstream effects of the pandemic on the health of the IS research ecosystem. This investigation surfaced a troubling phenomenon that we coined “the IS scholarly divide”. This editorial develops the theoretical underpinnings for the scholarly divide and posits the taxonomy of the divide. Finally, we explore the effects and forward some possible remedies.